The Influence of Recruitment, Selection, and Work Placement on Non-Civil Servant Staff Performance Case Study of Hasanuddin University (Unhas) - Sri Wahyuningsi; Nurdjanah Hamid; Djumidah Maming (Magister Management, Hasanuddin University, 2020)
This research aims to investigate and analyze the effect of recruitment, selection, and the work placement against the performance of the non-government officials of Hasanuddin University (UNHAS). Data were collected through distributed questionnaires which were then analyzed their validity test and reliability test afterward. The study applied multiple linear regression analysis with the classical assumption test conducted in the first place. The research results indicate that the recruitment, the selection, and the work placement had a positive and significant effect on the educational staff performance of Hasanuddin University Makassar.